Interplanetary coronal mass ejection observed at STEREO-A, Mars, comet 67P/Churyumov-Gerasimenko, Saturn, and New Horizons en route to Pluto: Comparison of its Forbush decreases at 1.4, 3.1, and 9.9 AU - Witasse,O; Sanchez-Cano,B; Mays,ML; Kajdic,P; Opgenoorth,H; Elliott,HA; Richardson,IG; Zouganelis,I; Zender,J; Wimmer-Schweingruber,RF; Turc,L; Taylor,MGGT; et al. (Journal of Geophysical Research: Space Physics, 2017)
We discuss observations of the journey throughout the Solar System of a large interplanetary coronal mass ejection (ICME) that was ejected at the Sun on 14 October 2014. The ICME hit Mars on 17 October, as observed by the Mars Express, Mars Atmosphere and Volatile EvolutioN Mission (MAVEN), Mars Odyssey, and Mars Science Laboratory (MSL) missions, 44 h before the encounter of the planet with the Siding-Spring comet, for which the space weather context is provided. It reached comet 67P/Churyumov-Gerasimenko, which was perfectly aligned with the Sun and Mars at 3.1 AU, as observed by Rosetta on 22 October. The ICME was also detected by STEREO-A on 16 October at 1 AU, and by Cassini in the solar wind around Saturn on the 12 November at 9.9 AU. Fortuitously, the New Horizons spacecraft was also aligned with the direction of the ICME at 31.6 AU. We investigate whether this ICME has a nonambiguous signature at New Horizons. A potential detection of this ICME by Voyager 2 at 110–111 AU is also discussed. The multispacecraft observations allow the derivation of certain properties of the ICME, such as its large angular extension of at least 116°, its speed as a function of distance, and its magnetic field structure at four locations from 1 to 10 AU. Observations of the speed data allow two different solar wind propagation models to be validated. Finally, we compare the Forbush decreases (transient decreases followed by gradual recoveries in the galactic cosmic ray intensity) due to the passage of this ICME at Mars, comet 67P, and Saturn.